Oral health status of children with intellectual and developmental disabilities in India: a systematic review and meta-analysis - Vini Mehta; Snehasish Tripathy; Yash Merchant; Ankita Mathur; Sapna Negi; Muhammad Aaqib Shamim; Shahabe Saquib Abullais; Mohammed A. Al-Qarni; Mohmed Isaqali Karobari (BMC Pediatrics)
Abstract Introduction India has committed to the Sustainable Development Goals (SDGs) 2030 principle of “Leave No One Behind”, which seeks to reduce disparities and vulnerabilities. The dearth of data on the oral health conditions of children with intellectual and developmental (IDD) disabilities in India is significant. Our systematic review intended to collate and synthesise data on the oral health status of children with IDD. Methods Online electronic databases such as PubMed-MEDLINE, Embase, and Scopus were searched using appropriate keywords from the earliest available data until 31st March 2024, with no language restriction. Cross-sectional studies conducted amongst individuals below 18 years of age with intellectual, or developmental disabilities, in India were included. Quality assessment and meta-analysis using a random-effects model for variables reported from four or more studies and a prediction interval was calculated. Results Out of 2388 studies, a total of 15 studies were included. Our study showed that 91% (95% [confidence interval] CI: 0.80–0.96) of IDD children use toothbrushes regularly. However, poor oral hygiene was found among 38% (95% CI = 0.21–0.59) of IDD children. The pooled prevalence of dental caries among children was found to be 64% (95% CI: 0.45–0.79). Periodontal disease was reported in only one study among 54.20% of IDD children. Conclusions Our findings suggest that despite brushing regularly the incidence of caries and poor oral hygiene in children with IDD is high. Flexible, tailored interventions that go beyond a uniform approach must be implemented to effectively address oral health requirements of children with IDD. Specific Health Programmes should be established for their preventive oral care.